Evaluation of the centesimal composition and drying temperature of Shiitake mushrooms (Research, Society and Development, 2022)
The present work aimed to determine the centesimal composition of Shiitake mushroom (Lentinula edodes), as well as to determine the best drying temperature. The mushrooms were dried in an air circulation oven at 45°C, 47.5°C and 50°C and weighed every 30 minutes in order to obtain a drying curve. Three repetitions were made. The samples submitted to 50°C showed greater loss of moisture in the drying time elapsed, indicating that this temperature has better performance. In the determination of the centesimal composition, the samples presented an average of 28.55% of proteins, a value within the values found in literature. For lipids and ashes the averages were 6.08% and 1.48%, respectively, values which are not compatible with those found in similar studies. The best drying temperature was 50º C, however more studies are needed on the drying process in order to determine more precisely the best parameters, as well as a deeper understanding of the influence of different substrates used in the composition of edible mushrooms.